Community-based prenatal screening for postpartum depression in a South African township - Hung, Kristin J. (2014)
OBJECTIVE: To assess the feasibility of using community health workers to administer short or ultra-short screening instruments during routine community-based prenatal outreach for detecting probable depression at 12 weeks postpartum. METHODS: During pregnancy and at 12 weeks postpartum, the 10-item Edinburgh Postnatal Depression Scale (EPDS-10) was administered to 249 Xhosa-speaking black African women living in Khayelitsha, South Africa. We compared the operating characteristics of the prenatal EPDS-10, as well as 4 short and ultra-short subscales, with the criterion standard of probable postpartum depression. RESULTS: Seventy-nine (31.7%) women were assessed as having probable postpartum depression. A prenatal EPDS-10 score of 13 or higher had 0.67 sensitivity and 0.67 specificity for detecting probable postpartum depression. Briefer subscales performed similarly. CONCLUSION: Community health workers successfully conducted community-based screening for depression in a resource-limited setting using short or ultra-short screening instruments. However, overall feasibility was limited because prenatal screening failed to accurately predict probable depression during the postpartum period.